Long-term effects of photobiomodulation therapy on blood pressure in obese rats induced by a high-fat diet - Oishi, Jorge Camargo; de Moraes, Luis Henrique Oliveira; Filho, Julio Cesar Conceição; de Moraes, Thiago Francisco; Terroni, Barbara [UNESP]; de Castro, Cynthia Aparecida; Almeida-Lopes, Luciana; Rodrigues, Gerson Jhonatan (Springer Nature, 2024)
The main cardiovascular disease risk associated with obesity is hypertension. The therapeutic use of photobiomodulation therapy (PBM) is suggested for the treatment of wound healing, osteoarthritis, and arterial diseases. However, few studies have measured how red laser (at 660 nm) acts over hypertension, and any of those studies used experimental obesity model. The aim of the study was an attempt to evaluate the long-term effect of PBM on systolic blood pressure in an animal model of obesity, induced by a high-fat diet (HFD). Our results indicate that PBM carried out 3 days a week was able to prevent the increase in blood pressure (133.75 ± 4.82 mmHg, n = 8) induced by a high-fat diet (150.00 ± 4.57 mmHg, n = 8; p < 0.05), restore nitric oxide levels (control: 31.7 ± 5.5 μM, n = 8; HFD + PBM: 29.9 ± 3.7 μM, n = 8 > HFD: 22.2 ± 2.9 μM, n = 8, p < 0.05), decrease lipoperoxidation (control: 1.65 ± 0.25 nM, n = 8; HFD + PBM: 2.05 ± 0.55 nM, n = 8 < HFD: 3.20 ± 0.47 nM, n = 8; p < 0.05), and improve endothelial function (pD2 control: 7.39 ± 0.08, n = 8 > pD2 HFD + PBM: 7.15 ± 0.07, n = 8 > HFD: 6.94 ± 0.07, n = 8; p < 0.05). Our results indicate that PBM prevents the elevation of blood pressure in an obese animal model by a mechanism that involves improvement of endothelial function through an antioxidant effect.
Keywords: Endothelial dysfunction; High-fat diet; Hypertension; Nitric oxide; Obesity; Photobiomodulation